Single‐incision laparoscopic surgery for giant hepatic cyst. Issue 3 (24th July 2013) - Gocho, Takeshi; Misawa, Takeyuki; Suzuki, Fumitake; Ito, Ryusuke; Shiba, Hiroaki; Futagawa, Yasuro; Wakiyama, Shigeki; Ishida, Yuichi; Yanaga, Katsuhiko
Abstract Introduction The aim of this study was to assess the feasibility and safety of single‐incision laparoscopic fenestration and to introduce a new surgical technique. Laparoscopic fenestration has become a standard approach for symptomatic hepatic cysts because of the low recurrence rate and minimal postoperative pain. The single‐incision laparoscopic surgery (SILS) technique has increasingly gained acceptance and is now applied to a variety of organs and operations. Materials and Surgical Technique Between February 2010 and March 2011, we consecutively performed six cases of single‐incision laparoscopic fenestration. A SILS Port was placed through a single intraumbilical skin incision. In addition to standard laparoscopic instruments, a flexible 5‐mm laparoscope and an articulating grasper were used. The cyst wall was dissected with a 5‐mm bipolar vessel sealer. SILS was successfully performed in all patients, and none required conversion to conventional multiport laparoscopic surgery or open surgery. Intraoperative blood loss was minimal in all cases. Median operative time was 144 min (range, 100–210 min). All patients were discharged uneventfully on 3 day postoperative. Median postoperative follow‐up at 15.5 months (range, 8–20 months) did not reveal any complications or recurrence. The umbilical incisions were almost unnoticeable. Discussion Our findings suggest that SILS for fenestration of a giant hepatic cyst is a safe and feasible. It is reproducible technique that is comparable to conventional laparoscopic surgery.